PESAN DAKWAH MELALUI PAKAIAN PADA FOTO JURNALISTIK (ANALISIS SEMIOTIKA PADA FOTO DEDI MULYADI DI MEDIA KOMPAS.COM) - Nazmi Abdurahman (ADISAM PUBLISHER, 2025)
Journalistic photography is not merely used to beautify a media page, but it also conveys a message. In the context of this research, the message is closely related to the clothing worn by Dedi Mulyadi, the Regent of Purwakarta, as featured on the online media platform (link unavailable) The clothing has signs and meanings that represent the wearer. Clothing as a sign plays a crucial role as a medium and material for communication. This research aims to describe the da'wah message in Dedi Mulyadi's clothing. This research employs Charles Sanders Pierce's semiotic theory to analyze the da'wah message in Dedi Mulyadi's clothing. The theory emphasizes three aspects: sign, object, and interpretation. This research is a qualitative study with an interpretive paradigm. To analyze the data, the semiotic method is used. Data collection is done through interviews and documentation. Based on the analysis results, it is concluded that the Sundanese pangsi clothing worn by Dedi Mulyadi is formed by three elements: beauty, simplicity, and humility, which reflect the Islamic teachings and Sundanese culture that values beauty, simplicity, and appreciation for differences. The third element is the result of acculturation between Islamic teachings and Sundanese culture, producing a new identity. This reality shows that da'wah can be done in various ways, including through traditional local clothing.